Genomic characterization of Achromobacter genogroup 20 and identification of a potential species-specific marker - Mariana Papalia; Rocio Stucchi; Valeria Alexander; Liliana Clara; Mariángeles Visus; Gabriel Gutkind; Marcela Radice (Journal of Global Antimicrobial Resistance)
Objective: To describe the genome of Achromobacter genogroup 20 and explore the presence of resistance determinants. Methods: Isolate 413638 was identified through nrdA and MLST analysis. Antimicrobial susceptibility testing was performed according CLSI 2024. NGS was conducted using Illumina MiSeq, on the NextSeq500 platform with 150 bp paired-end reads, and de novo assembly was assessed using Unicycler (Galaxy). Coding sequences were predicted and confirmed with RAST and BLAST, and resistance determinants were evaluated using Resfinder and manual curation. All Achromobacter spp. genomes were obtained from NCBI, and the presence of blaOXA was investigated. Average nucleotide identity (ANI) and tetranucleotide analysis (TETRA) were calculated. Phylogenetic analysis of the new OXA variant was conducted against other species-specific markers in Achromobacter. Results: Isolate 413638 was identified as Achromobacter genogroup 20 ST365, showing resistance to third- and fourth-generation cephalosporins, aminoglycosides, and fluoroquinolones. The genome included coding sequences for three putative β-lactamases (one new OXA type-class D β -lactamase and two new class C), 32 efflux pump proteins, two aminoglycoside-modifying enzymes and a dihydropteroate synthase; also, substitutions in parC and parE were detected. The OXA enzyme, designated OXA-1238 (PP446293), differs from OXA-114a by 85 amino acids, with 69% identity. In silico analysis found OXA-1238 variants in three additional Achromobacter spp. genomes, with 97% identity. Based on ANI and tetra analysis, the three genomes corresponded to Achromobacter genogroup 20. Conclusion: Several resistance markers were found, probably contributing to the resistance profile observed in Achromobacter genogroup 20 ST365. The new OXA variant identified, OXA-1238, could constitute a useful molecular marker for species identification.